2016
DOI: 10.18632/oncotarget.12211
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of RAD51B, XRCC3 and other homologous recombination genes is associated with expression of immune checkpoints and an inflammatory signature in squamous cell carcinoma of the head and neck, lung and cervix

Abstract: Immune checkpoints are emerging treatment targets, but mechanisms underlying checkpoint expression are poorly understood. Since alterations in DNA repair genes have been connected to the efficacy of checkpoint inhibitors, we investigated associations between methylation of DNA repair genes and CTLA4 and CD274 (PD-L1) expression.A list of DNA repair genes (179 genes) was selected from the literature, methylation status and expression of inflammation-associated genes (The Cancer Genome Atlas data) was correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Forty-one genes, including two principal DDR genes (BRCA1 and BRCA2), 37 additional DDR genes (FANCD2, BAP1, ATR, RAD17, XRCC4, RAD50, RAP80, FANCE, MLL3/XRCC2/PTIP, WRN, NBS1, PTEN, FANCF, MRE11A, ATM, CHEK1, FANCM, RAD51B, XRCC3, RAD51, TP53BP1, MRG15/BLM, ERCC4, PALB2, PAGR1, FANCA, RAD51D, CDK12, RAD51C, BRIP1, MLL4, ERCC1/2, and CHEK2), two oncogenes (MYC and CCNE1), and one checkpoint and apoptosis gene (TP53) were selected to analyze genomic aberrations (gains, amplifications, losses, and UPDs) because previous studies reported the involvement of these genes in the DDR pathway or genomic instabilities. 1,3,8,9,[19][20][21][22][23][24][25][26] The numbers of the four chromosome aberrations (gains, losses, amplifications, and UPDs) were examined in each tumor. Gains and amplifications in two oncogenes (MYC and CCNE1) were individually analyzed; however, they were combined and referred to as amplifications in subsequent sections.…”
Section: Copy Number and Loss Of Heterozygosity (Loh) Analysis Usinmentioning
confidence: 99%
“…Forty-one genes, including two principal DDR genes (BRCA1 and BRCA2), 37 additional DDR genes (FANCD2, BAP1, ATR, RAD17, XRCC4, RAD50, RAP80, FANCE, MLL3/XRCC2/PTIP, WRN, NBS1, PTEN, FANCF, MRE11A, ATM, CHEK1, FANCM, RAD51B, XRCC3, RAD51, TP53BP1, MRG15/BLM, ERCC4, PALB2, PAGR1, FANCA, RAD51D, CDK12, RAD51C, BRIP1, MLL4, ERCC1/2, and CHEK2), two oncogenes (MYC and CCNE1), and one checkpoint and apoptosis gene (TP53) were selected to analyze genomic aberrations (gains, amplifications, losses, and UPDs) because previous studies reported the involvement of these genes in the DDR pathway or genomic instabilities. 1,3,8,9,[19][20][21][22][23][24][25][26] The numbers of the four chromosome aberrations (gains, losses, amplifications, and UPDs) were examined in each tumor. Gains and amplifications in two oncogenes (MYC and CCNE1) were individually analyzed; however, they were combined and referred to as amplifications in subsequent sections.…”
Section: Copy Number and Loss Of Heterozygosity (Loh) Analysis Usinmentioning
confidence: 99%
“…41 It is possible that RAD51B deficiency increases the mutational burden of tumors through HRD, potentially making these patients good candidates for immunotherapy due to their increased likelihood of harboring neoantigens. 53 Taken together, these findings suggest that genetic ancestry may play an important role in mutational development and cancer progression. This highlights the need to accumulate more genetic data from diverse populations in order to better understand the heightened aggressive breast cancer risk observed in individuals of African ancestry.…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown that loss‐of‐function mutations in homologous recombination genes other than BRCA1/2 can facilitate HRD signature activity . It is possible that RAD51B deficiency increases the mutational burden of tumors through HRD, potentially making these patients good candidates for immunotherapy due to their increased likelihood of harboring neoantigens . Taken together, these findings suggest that genetic ancestry may play an important role in mutational development and cancer progression.…”
Section: Discussionmentioning
confidence: 96%
“…Homologous recombination repair (HRR) is the leading DNA repair mechanism of double-strand DNA breaks (DSB) that uses the homologous region of the sister chromatid as the replicative template in order to reliably repair DSB [16]. RAD51 protein has an important activity in HRR, promoting the insertion of the broken ends of the DSB into the sister chromatid [17,18]. Its action is dependent on RAD51-like proteins: RAD51B, RAD51C, RAD51D, XRCC2 and XRCC3 [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…RAD51 protein has an important activity in HRR, promoting the insertion of the broken ends of the DSB into the sister chromatid [17,18]. Its action is dependent on RAD51-like proteins: RAD51B, RAD51C, RAD51D, XRCC2 and XRCC3 [17][18][19]. Defects in the HRR pathway entail cell proliferation despite DNA damage, promoting cancer development [20].…”
Section: Introductionmentioning
confidence: 99%